Chi3l1 induction in Response to LPS Suppresses Osteoblast Apoptosis (Global Journal of Science Frontier Research, 2017)
Upregulation of Chitinase-3-like protein 1(Chi3l1), a member of glycohydrolase family 18, is frequently seen in diseases associated with inflammatory responses, such as atherosclerosis, meningitis and asthma. However, little is known about either its regulation or its functions in the physiological and pathological processes in bone and related cells. In the mouse model of osteomyelitis used in this study, Chi3l1 was induced in the infected area. In vitro stimulation of osteoblasts and mesenchymal stem cells (MSCs) by lipopolysaccharide (LPS) resulted in elevated Chi3l1 expression. Overexpression of Chi3l1 attenuated TNFα-induced osteoblast apoptosis and promoted cell survival. Furthermore, Chi3l1 induced phosphorylation of AKT in a time-dependent fashion, while an inhibitor of the AKT signaling pathway abolished both the pro-survival and the anti-apoptotic effects of Chi3l1. Therefore, Chi3l1 might play a protective role in infected or inflammatory bone tissues by suppressing osteoblast apoptosis via an AKTdependent pathway.
Keywords: AKT; apoptosis; chitinase-3-like protein 1; LPS; TNFα